Dataset: Resurgence of superconductivity and the role of the dxy hole band in FeSe1−xTex - Morfoot, A; Kim, T; Coldea, A I (University of Oxford, 2023)
This dataset is related to the publication entitled: "Resurgence of superconductivity and the role of the dxy hole band in FeSe1−xTex" to appear in Communication Physics. The data files are either ARPES data collected to the Diamond Light Source (.nxs files), ASCII files with the extracted paramaters (.dat) or structural files used as input in DFT calculations (.struct). The PDF files of each figures are provided.